Efektivitas Teknik Mind Mapping dalam Layanan Bimbingan Kelompok untuk Meningkatkan Kemampuan Perencanaan Karir Siswa - Rizqi, Salistina Ayu; Putro, Hijrah Eko; Indiati, Indiati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this study was to test the effectiveness of mind mapping techniques in group guidance services to improve the career planning skills of eighth grade students of SMP N 3 Bulu Temanggung. This type of research is a quantitative research with an experimental method of one group pre-test post test design. This research was conducted in eight meetings with 8 students as research subjects. The data analysis technique used parametric analysis and paired sample t-test. The results showed that there was a change in students' career planning before and after participating in group guidance services with mind mapping techniques (Sig. (2-tailed) = 0.00 < 0.05). This shows that the mind mapping technique with group guidance services is effective for improving the career planning skills of eighth grade students of SMP N 3 Bulu Temanggung. For this reason, Bk teachers should use mind mapping techniques in group guidance services to improve students' career planning skills.